ChemInform Abstract: Synthesis, Characterization, and Tribological Properties of Two‐Dimensional Ti3C2. Issue 2 (January 2015) - Yang, Jin; Chen, Beibei; Song, Haojie; Tang, Hua; Li, Changsheng
Abstract Two‐dimensional Ti3C2 is prepared by exfoliation of Ti3AlC2 powders (obtained by sintering of Ti, Al, and graphite at 1350 °C for 2 h under flowing Ar) with HF solution at room temperature for 20 h.